1-Nitro-2-trinitromethyl substituted imidazoles: a new family of high performance energetic materials. Issue 45 (7th November 2016) - Xu, Yuangang; Shen, Cheng; Lin, Qiuhan; Wang, Pengcheng; Jiang, Chao; Lu, Ming
Abstract : A series of trinitromethyl-substituted imidazole energetic materials that achieved a fine balance between high performance and low sensitivity were synthesized. Abstract : A new series of 1-nitro-2-trinitromethyl substituted imidazoles were designed and synthesized. All the compounds were characterized by multinuclear NMR and IR spectroscopies, elemental analysis (EA), and differential scanning calorimetry (DSC). X-ray structure determination of compounds11–15, 17 and19 showed that their densities range from 1.59 g cm −3 to 1.86 g cm −3 and gave insights into their structural characteristics showing the presence of extensive hydrogen-bonding interactions. Most of these new materials exhibit positive heats of formation (HOF = 145.7–344.8 kJ mol −1 ), acceptable oxygen balances and sensitivity values (IS = 10.4–32.5 J, FS = 85–240 N). Detonation velocities ( D ) and pressures ( P ) were calculated with EXPLO5 V6.01 based on the calculated HOF and densities indicating that some of these trinitromethyl materials ( D = 8688–8764 m s −1, P = 34.4–35.1 GPa) are comparable to 1, 3, 5-trinitroperhydro-1, 3, 5-triazine (RDX, D = 8795 m s −1, P = 34.9 GPa). Among the new derivatives, 17 ( ρ = 1.82 g cm −3, Δ H f = 145.7 kJ mol −1, D = 8764 m s −1, P = 35.1 GPa, IS = 14.5 J, OB = 5.0%) shows potential as a high performance energetic material.